PERILAKU PETANI DALAM PENGENDALIAN HAMA TERPADU PADA BUDIDAYA PADI DI KECAMATAN CIKEDUNG - Lukman Effendy; Muhamad Tassim Billah; Doni Darmawan (Sekolah Tinggi Pariwisata Mataram, 2020)
Pest control is one of the methods used to treat and control pest attacks. To change the behavior of farmers can be transformed which leads to the knowledge, attitude and skill of farmers about PHT in the cultivation of rice. So the writer would raise the title of the farmer's behavior in the unified pest control (UPC) of raising rice (Oryza sativa) in the district district district district district district.